Groundwater Quality of Open Wells and Tube Wells around Amalner Town of Jalgaon District, Maharashtra, India - V. T. Patil; P. R. Patil (E-Journal of Chemistry)
Groundwater samples (Three open wells, three tube wells) were collected from six different locations around Amalner town and analyzed during November 2007-February 2008. Fifteen physicochemical parameters were analyzed and the results were compared with water quality standards prescribed by WHO and ISI 10500-91. In the present study, two water samples (one open well, one tube well) showed high EC, TDS, TA, TH values indicating poor water quality. The correlation coefficients were calculated. The significance of the results is further discussed.